Malaysian undergraduates' (in) ability to identify the correct use of sources / Ho Chui Chui and Wong Soon Heng - Ho, Chui Chui; Wong, Soon Heng (Universiti Teknologi MARA, Kedah, 2014)
Studies conducted in the West show that one of the reasons students plagiarize is because of their poor understanding of the correct use of sources. This paper reports on a small-scale study which assessed whether Malaysian law matriculation students could identify the correct use of sources. Findings show that 66% of the respondents did not know that quoting without using quotation marks was an example of the incorrect use of a source although the source was acknowledged. Similarly, 66% also felt that a source was correctly used although it was poorly paraphrased with only slight modification as long as the source was cited. The results indicate that these Malaysian undergraduates have a poor understanding about the proper use of sources and may inadvertently be committing plagiarism.